Implementasi Manajemen Waktu dalam Membangun Habiutas Siswi di MA Nurul Jadid Program IPA Tahfidz - Abdullah Abdullah; Helmiyatul Mufidah (LP. Ma'arif Janggan Magetan, 2023)
The time management of MA Nurul Jadid Probolinggo students of the Tahfidz Science program is still a problem, where it can be known that not all Tahfidz Science students can achieve the target on time determined by the school. One way to overcome these problems is by habituating time management in female students, this study aims to determine the influence of time management in overcoming the problem of achieving the target of MA Nurul Jadid students of the TAHFIDZ Science Program. This research design uses descriptive qualitative methods observed directly in the field, so the data produced is in the form of description writings not in the form of numbers. This qualitative study focuses on planning, organizing, implementing and impacting the management of learning disciplines on female students, as well as the factors that hinder it. The results showed that MA Nurul Jadid students of the TAHFIDZ Science Program did not pursue airing for khatam but to strengthen memorization, namely with the assembly system, namely the tasmi method.